Job Connectedness Causing Poor-sleep and Work-family Conflicts in Professionals? The Moderating Role of Emotion Regulation: A Conceptual Framework - Dr. Deeba Hasan; T J Kamalanabhan (Journal of Management Research, 2024)
The common practice of connecting to one’s job outside the primary office by using ICTs is linked to adverse outcomes like work-family conflict and poor-sleep quality. However, outcomes are shown to vary between individuals. This work aims to establish the root cause behind individual variations by unearthing the foundational generative mechanisms that lead to the outcomes. The ontological and epistemological approach of critical realism is used to propose a novel conceptual framework that offers a three-way interaction effect between psychological control over work-life balance, emotion regulation strategies and job-connectedness outcomes. According to the framework positive emotion regulation generated by the appropriate use of savoring and dampening strategies elicits specific neurobiological processes that mitigate adverse outcomes of job-connectedness. This work theoretically extends Bandura’s agentic perspective of socio-cognitive theory and practically provides managers with a deep understanding of the generative forces underlying human functioning that can be leveraged for hiring, leadership development and performance-management. An additional contribution of this work is providing a taxonomy of traditionally interchangeably-used terms to denote different kinds of alternate work arrangements, thus clearing the prevalent ambiguity in literature. A research limitation is the theoretical nature of the framework that needs to be tested empirically to confirm the effect sizes of the proposed relationships. This work is timely and offers future research directions in the interdisciplinary fields of IS and psychology.